Bean plastic - Costa, Joaquim Geraldo Cáprio da; Kohashi-Shibata, Josue; Colin, Salvador Miranda (Pesquisa Agropecuaria Brasileira, 2014)
The influence of population densities on the plasticity of beans (Phaseolus vulgaris L.) was studied through number of branches, number of nodes, number of seeds and total leaf area per plant, determined at the end of the growth cycle. Four bean cultivars were used: Canário 107, a determinate bush-type; Michoacan 12-A-3, an indeterminate short-vine, erect type, and Negro 150 and Flor de Mayo X-16441, both of them indeterminate, long-vine, climbing type. The indeterminate bus-type Canário 107 showed lower plasticity than the indeterminate type cultivars and is expected to increase the grain yield with increasing population density. Among the indeterminate types, the short-vine erect type Michoacan 12-A-3 showed lower plasticity than the long-vine cultivars Negro and Flor de Mayo X-16441.